Exigência de metionina mais cistina em dietas para tambaqui (Colossoma macropomum) de 55 a 118 g - AROUCHA, Rômulo Jordão Neves (2022)
Tambaqui is the most reared native species in Brazil, but the requirement for some essential amino acids at different rearing stages is still unknown, especially methionine plus cystine. Thus, the objective was to determine the requirement of methionine plus digestible cystine in diets for tambaquis, in the phase between 55 and 118 grams. 288 tambaquis with initial weight of 54.53 ± 0.15 grams were used, distributed in a completely randomized design, with six treatments and four replications and 12 fish per experimental unit, with a duration of 60 days. The treatments consisted of diets containing five levels of methionine plus digestible cystine (0.400; 0.600; 0.800; 1.000; 1.200%) formulated using the diet dilution technique and a control diet containing 0.600%, obtained from the supplementation of 0.202% of methionine plus cystine in the form of DL-methionine (99%) in the diet containing 0.400%. The fish were kept in polyethylene boxes with a capacity of 1000 liters, equipped with an individual water supply, aeration and drainage system. Zootechnical performance, body composition, protein, ash and body fat depositions, and nitrogen retention efficiency were evaluated. The control diet provided better feed conversion, higher body protein deposition and better nitrogen retention efficiency in fish compared to those fed with the lowest evaluated level. The increase in the dietary level of methionine plus digestible cystine influenced all variables evaluated in the study, except feed intake. Consumption of methionine plus cystine increased linearly and weight gain, specific growth rate and feed conversion improved quadratically, up to estimated levels of 0.876%, 0.883% and 0.907% of digestible methionine plus cystine, respectively. For body protein, a linear effect was observed, and quadratic effects for moisture, fat and body ash, with optimal levels estimated at 1.020%, 0.930% and 0.889%, respectively. Depositions of body protein, fat and body ash showed quadratic effects up to values estimated at 0.920%, 1.124% and 0.879% of digestible methionine plus cystine, respectively. It was concluded that the requirement for methionine plus digestible cystine in diets for tambaquis between 55 and 118 grams is 0.920% (0.297 g/Mcal of digestible energy), as it provides greater deposition of body protein.